Digitalization of Facility and Infrastructure Management to Improve School Management Effectiveness - Benny Alidasril; Arwan Saputra; Salsabila Azizah; Syafaruddin (Journal of Practice Learning and Educational Development, 2026)
The management of school facilities and infrastructure is still largely done manually, leading to various problems such as inaccuracies in inventory data, low work efficiency, and a lack of transparency and accountability in the management of educational assets. This research aims to analyze the role of digitalization in the management of facilities and infrastructure in improving the effectiveness of school management. The research method used is a qualitative approach thru literature study by examining various scientific sources such as journals, books, and relevant documents. Data analysis was conducted thru the stages of data reduction, data presentation, and conclusion drawing. The study results show that the digitization of facility and infrastructure management can improve the accuracy of inventory recording, the efficiency of administrative processes, and support data-driven decision-making. In addition, the implementation of digital systems contributes to the improvement of transparency, accountability, and sustainability in school asset management. However, the implementation of digitalization still faces challenges such as limited digital literacy among human resources, technological infrastructure, and institutional policy support. Therefore, digitalization needs to be implemented in a planned and sustainable manner to optimally enhance the effectiveness of school management.